Dynamic finite element simulation of dental prostheses during chewing using muscle equivalent force and trajectory approaches. (19th May 2017) - Razaghi, Reza; Biglari, Hasan; Karimi, Alireza
Abstract: The long-term application of dental prostheses inside the bone has a narrow relation to its biomechanical performance. Chewing is the most complicated function of a dental implant as it implements different forces to the implant at various directions. Therefore, a suitable holistic modelling of the jaw bone, implant, food, muscles, and their forces would be deemed significant to figure out the durability as well as functionality of a dental implant while chewing. So far, two approaches have been proposed to employ the muscle forces into the Finite Element (FE) models, i.e. Muscle Equivalent Force (MEF) and trajectory. This study aimed at propounding a new three-dimensional dynamic FE model based on two muscle forces modelling approaches in order to investigate the stresses and deformations in the dental prosthesis as well as maxillary bone during the time of chewing a cornflakes bio. The results revealed that both contact and the maximum von Mises stress in the implant and bones for trajectory approach considerably exceed those of the MEF. The maximum stresses, moreover, are located around the neck of implant which should be both clinically and structurally strong enough to functionally maintain the bone-implant interface. In addition, a higher displacement due to compressive load is observed for the implant head in trajectory approach. The results suggest the benefits provided by trajectory approach since MEF approach would significantly underestimate the stresses and deformations in both the dental prosthesis and bones.